A Pragmatic Study Of Gratitude And Thanking Expressions Used By Iraqi People - Fatima Farooq Jasim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The present study deals with Arabic gratitude and thanking expressions used by Iraqi people from a pragmatic perspective. It aims to investigate the expressions used by Iraqi people, in particular, and to show the gender difference in the ways men and women linguistically communicate gratitude in Iraqi culture. Accordingly, two hypotheses are proposed: first, Iraqi people use different thanking strategies; second, males and females differ in how they express gratitude to others. To verify the proposed hypotheses, a discourse completion task comprising 16 daily situations adapted from Eisenstein and Bodman (1993) is used to collect data. The designed completion task is given to 50 Iraqi participants (25 males, 25 females) aged 20 to 40 years. The responses are coded and analyzed according to the coding scheme proposed by Cheng (2005), which consists of 8 strategies for expressions of gratitude. Then Leech's politeness principle (1983) is applied to the collected responses. The results show that Iraqi people use different strategies for thanking and expressing gratitude, with thanking and prayer strategies being the most frequent. Other cultures haven’t used the prayer strategy; it has been found exclusively in Iraqi culture, and this is the gap that this study fills. Basically, prayer strategy hasn’t been stated in Cheng's (2005) model; thus, it can be added to modify the model to include 9 strategies for expressions of gratitude. Moreover, the study concludes that there are slight gender differences in expressing thanks and gratitude by Iraqi males and females, and what affects these differences are social roles, familiarity, and the degree of imposition; that is to say, the overall context can shape and determine one’s use of thanking and gratitude expressions.